La ética y lo ecosocial en el ejercicio del periodismo (2020)
A publication more than necessary to unlearn some "routines" that are in the journalistic exercise when it tries to address socially sensitive issues. When the web, virtual networks, some media, many politicians and a significant part of the people fuel false truths and hoaxes that “contaminate” the formative action of information, the Ecosocial Transition Guide and ethical principles for our media can make it a reference tool to look at before writing and publishing.